Improving Dance Skills Through Online Learning - Intan Ayu Febrianti; Ayo Sunaryo; Heny Rohayani; Dewi Karyati (Journal of Dance and Dance Education Studies, 2023)
Dance has a role as a medium of expression, creative thinking, developing talents, and also a medium of communication. During the pandemic, the dance studio was also affected, namely not being able to carry out face-to-face learning. One of the efforts that could be made was by conducting online learning. For dance learning through online learning, utilizing internet applications as a medium for mutual interaction and learning, one of which was the Google Meet application, the advantages of the Google Meet application for online dance training include this application which can be downloaded and used free of charge so that anyone with a gadget can access this application. Research conducted using experimental methods with a quantitative approach, Pre-Experimental design research design with the category of one group pretest-posttest design. The samples used in this study were 20 people with different age levels, from the age range of 7 to 17 years. Based on the results of the study, the average values for each meeting were 75.5, 81 and 92.5. At the third meeting, the student assessment criteria were rated (A) very well, with the resulting average score increasing rapidly and being in very good criteria, this was because students were able to perform dances well and their dancing skills increased at each meeting.